Crumb : show the dough who's boss - Bertinet, Richard (Kyle Books, 2019)
Bread can be open and airy or compact and dense - it is all about the 'crumb' which characterises particular styles of loaf. In this inspiring new book, Richard Bertinet shares his hallmark straightforward approach to making bread through every step of the process, including the various techniques of fermenting, mixing, kneading and baking. Richard shows you how to make everything from classic and rustic breads to sourdough using different flours and ferments. Learn how to bake a range of delicious sweet and savory recipes from Manchego & Chorizo Cornbread, Seaweed & Sel Gris Rolls and Chickpea Flatbreads to Orange & Cardamom Swirls and Cinnamon Buns. There are also options for gluten-free breads and the best bakes to improve your gut-health by experimenting with different types of flour. Finally, Richard shares ideas for cooking with bread and creams, syrups and purées to enjoy alongside or incorporate into your bakes. With stunning step-by-step photography, simple advice and helpful techniques throughout,